O vazio da união das culturas nipo-brasileira: projeto no bairro da Liberdade-SP - Kajiwara, Sheila Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The work aims at an architectural project in the neighborhood of Liberdade in Sao Paulo, from analysis of the spread of Japanese culture in Brazil. Within this theme, the paper focuses on the Japanese urban space and the search for an identity of the Japanese, besides the problems that the neighborhood has. The architectural design is justified by the need for spaces of rest, meetings and green areas, where people can get away a bit of pace that the neighborhood has. The source of this research is based on bibliographic references, reviews of other projects, investigating the experience of urban space and the richest source of contributions that were the memories of living in Japan for eight months. The expected result is the visualization of the project through sketches, experiments and artistic designs for the chosen location

O trabalho tem por objetivo um projeto arquitetônico no Bairro da Liberdade, em São Paulo, a partir de análises da difusão da cultura japonesa no Brasil. Dentro desta temática, o trabalho aborda o espaço urbano japonês e a busca de uma identidade pelos imigrantes japoneses, além das problemáticas que o bairro apresenta. O projeto arquitetônico se justifica pela necessidade de espaços de descanso, encontros e áreas verdes, onde as pessoas possam se afastar um pouco do ritmo acelerado que o bairro possui. A fonte de pesquisa consiste em referências bibliográficas, análises de outros projetos, averiguação da vivência do espaço urbano e a mais rica fonte de contribuição que foram as memórias do morar no Japão durante oito meses. O resultado esperado é a visualização do projeto através de croquis, experimentações e desenhos artísticos para o local escolhido
Keywords: Imigrantes; Japoneses; Identidade; Japanese immigration; Identity; Cultural values